Nanocrystalline Copper Oxide(II)-Catalyzed Alkyne-Azide Cycloadditions - 송영진; 유충열; 홍종태; 김승주; 손승욱; 장혜영 (Bulletin of the Korean Chemical Society, 2008)
Although the use of Cu(II) salts as catalysts without reductants is limited in the cycloaddition of acetylenes with azides, the catalytic system employing average 10 nm CuO(II) nanoparticles in the absence of reductants shows good catalytic activity to form 1,4-disubstituted 1,2,3-triazoles even in wet THF as well as water. It is also noticeable that CuO(II) nanoparticle catalysts can be recycled with consistent activity. A range of alkynes and azides were subject to the optimized CuO(II) nanoparticle-catalyzed cycloaddition reaction conditions to afford the desired products in good yields. KCI Citation Count: 37